Ajuste da planta de processos da plataforma de pampo usando análise pinch - Brescansin, José Valdir (1997)
This work presents the retrofitting of the Pampo offshore process plant which is situated em Campos Bay and belongs to PETROBRAS. Only few energetic integration was considered in the original design of this platform. As a result of the discovery of new oil wells the plant hot utility generation system has became overloaded. Thus, a study for better utilisation of the available energy in the process streams of this plant is required. Initially, it was proposed a method to adjust the operating plant. This method, which is more conservative than those presented in the literature, hás lead to results closer to the practical reality PTT software, developed by PETROBRAS and the SUPERTARGET software from Linnhoff March Co., were used to adjust the plant while the HYSIM simulator was used to calculate the heat exchangers. Results demonstrate that an investment of the US$ 1,35 millions make it is possible to achieve an overall saving US$ 1,46 millions/years. This saving is related to the natural gas, which would be burned to produce of the hot utility. The returning time for this investment is around 11 months. The implementation of the suggestions proposed in this work should solve the energy shortage problem for processing the new oil just with one heat exchanger, remaining the two existent exchangers as spare ones.